2017
DOI: 10.5301/jabfm.5000359
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Healing of Periapical Lesions after Unintentional Extrusion of Mineral Trioxide Aggregate

Abstract: The unintentional extrusion of MTA does not prevent the healing of periapical lesions, but may be a delaying factor for periapical healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(84 reference statements)
1
10
0
Order By: Relevance
“…[ 14 ] They found that at follow-up, the tooth was asymptomatic after MTA extrusion in molar and at repair of the lesion was evident radiographically. Our results were also in accordance with the study performed by Demiriz et al .,[ 15 ] who showed that MTA extrusion was reduced in 85% and was almost absent in 10% teeth compared with 84% and 12%, respectively, in our study.…”
Section: Discussionsupporting
confidence: 50%
“…[ 14 ] They found that at follow-up, the tooth was asymptomatic after MTA extrusion in molar and at repair of the lesion was evident radiographically. Our results were also in accordance with the study performed by Demiriz et al .,[ 15 ] who showed that MTA extrusion was reduced in 85% and was almost absent in 10% teeth compared with 84% and 12%, respectively, in our study.…”
Section: Discussionsupporting
confidence: 50%
“…Traumatic dental injuries leading to pulp necrosis and apical periodontitis were the most common reason for treatment in both RET and MTA study groups. Exhaustive data about the specific type of trauma injury were reported in five of the included studies (Bucher et al 2016 ; Ree and Schwartz 2017 ; Kandemir Demirci et al 2019 ; Chan et al 2017 ; Ulusoy et al 2019 ), and two studies did not state the cause for the treatment (Demiriz and Hazar 2017 ; Mente et al 2013 ). In both study groups, the overall trauma frequency varied between 46 and 100% (Table 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…one to four weeks—with the exception of a prolonged time frame in one of the control groups where the final treatment was postponed until a complete apical calcific barrier was observed radiographically and confirmed clinically (Kandemir Demirci et al 2019 ). Two of the MTA studies did not provide data about the total medication time (Demiriz and Hazar 2017 ; Mente et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microorganisms are found close to or in the root canal system or at the outside around the root apex (3)(4). Carious and trauma are the most common reasons for the inflammation or necrosis of the pulp tissue in permanent teeth (5). It is recognized that the healing of these lesions depends on proper mechanical and chemical removal of the infected canal content, as well as three-dimensional canal obturation (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%